Analisis Potensi Interaksi Obat Golongan Antidepresan pada Pasien Skizofrenia di Rumah Sakit Jiwa Dr. Soeharto Heerdjan Tahun 2016 - Puspitasari, Atika Wahyu; Angeline, Loranda (Pharmaceutical Sciences and Research, 2019)
Schizophrenic patients who used antidepressant combination drug therapy in their treatment can cause drug interaction. This study aimed to determine the potential drug interactions of antidepressant in schizophrenic patients. The study designed was cross-sectional by random sampling. The samples were secondary data from outpatient prescriptions and medical record of schizophrenic patients in Psychiatric Hospital Dr. Soeharto Heerdjan during 2016. From 743 drug prescriptions, it was found that 694 (91.41%) drug prescriptions having 1286 (61.24%) cases of drug interaction. The most common interaction were fluoxetine and risperidone in 376 cases (29.24%). The proportion based on interaction level was 1246 cases (96.89%) for severe, 34 cases (2.64%) for moderate, and 6 cases (0.47%) for minor. The study concluded that antidepressant prescribing needs to be closely monitored because of high incidence in drug interactions or modified when the negative impact was greater than the positive impact.